A stepwise approach to designing and delivering the SCHeLTI trial community-family-mother-child obesity prevention intervention - Olivia De-Jongh González; Jianxia Fan; Isabelle Marc; Hong Jiang; Andraea Van Hulst; Claire N. Tugault-Lafleur; Yanting Wu; Yanhui Hao; Liping Wang; Xiaoyu Hu; Caifeng Wang; Wenguang Sun; et al. (MethodsX)
This paper describes the methods for the development and implementation of the Sino-Canadian Healthy Life Trajectories Initiative (SCHeLTI) intervention, part of a World Health Organization-supported effort to prevent childhood obesity through four international randomized controlled trials. SCHeLTI is a multi-center, cluster-randomized trial in Shanghai, supporting 4500 families from preconception through the child’s fifth year. This Community-Family-Mother-Child intervention includes coordinated components such as Healthy Conversation sessions, nutrition consultations, breastfeeding support, an obesity clinic, and educational courses tailored to key reproductive and developmental stages and risk profiles. Guided by implementation science principles, SCHeLTI’s development followed four main phases: 1) establishing the conceptual foundation (theoretical framework, outcomes, logic model); 2) building delivery infrastructure and engaging stakeholders in formative research; 3) finalizing the intervention design tailored to families’ needs; and 4) implementing the intervention, including capacity building, adaptation, and process evaluation strategies. • A four-phase development process grounded in implementation science principles guided intervention design and delivery • Tailored components align with reproductive and developmental stages and risk profiles to support family and child needs across the life course • Stakeholder engagement and iterative adaptation ensured contextual relevance and feasibility